2020
DOI: 10.1111/jbi.13764
|View full text |Cite
|
Sign up to set email alerts
|

The global distribution of grass functional traits within grassy biomes

Abstract: Aim The sorting of functional traits along environmental gradients is an important driver of community and landscape scale patterns of functional diversity. However, the significance of environmental factors in driving functional gradients within biomes and across continents remains poorly understood. Here, we evaluate the relationship of soil nutrients and climate to leaf traits in grasses (Poaceae) that are hypothesized to reflect different strategies of resource use along gradients of resource availability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 56 publications
(93 reference statements)
1
31
1
Order By: Relevance
“…The scheme makes it possible to translate the observed interspecific differences into practical guidance in ways that are not currently captured by the heuristic literature. Whilst quantitative associations between climate and traits were not part of this study, the traits recorded in this study appear to support hypotheses generated by Jardine et al (2020) and Watkins et al (2020): for example, in a study of 5 bottomland species, Nash and Graves (1993) found that M. virginiana was well-suited to urban environments with high oxygen and nutrient availability. A wider implication from this scheme is that it appears many of the species currently recommended for urban planting may need to be investigated in greater detail, with comparatively few species appearing to be suitable for planting in stressful, paved environments.…”
Section: Toward a Functional Trait Scheme For Urban Forestrysupporting
confidence: 68%
“…The scheme makes it possible to translate the observed interspecific differences into practical guidance in ways that are not currently captured by the heuristic literature. Whilst quantitative associations between climate and traits were not part of this study, the traits recorded in this study appear to support hypotheses generated by Jardine et al (2020) and Watkins et al (2020): for example, in a study of 5 bottomland species, Nash and Graves (1993) found that M. virginiana was well-suited to urban environments with high oxygen and nutrient availability. A wider implication from this scheme is that it appears many of the species currently recommended for urban planting may need to be investigated in greater detail, with comparatively few species appearing to be suitable for planting in stressful, paved environments.…”
Section: Toward a Functional Trait Scheme For Urban Forestrysupporting
confidence: 68%
“…Ignoring ITV and considering only the influence of turnover in species composition, there was nearly no AP–Height relationship. This contrasts with results for all plants at global and continental scales (Bruelheide et al., 2018; Moles et al., 2009; Šímová et al, 2018), and with grasses at a global scale (Jardine et al., 2020; Sandel et al., 2016) and regional scale (Forrestel et al, 2017). However, it is consistent with a previous study of California grasses (Sandel & Dangremond, 2012) and grasses within the San Francisco Bay Area (Sandel & Low, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…At a global scale, taller grass species with larger leaves tend to be found in warmer and wetter climates (Jardine et al., 2020; Sandel et al., 2016). Globally, high SLA has also been weakly associated with warmer temperatures (Sandel et al., 2016), although a different approach revealed essentially no relationship (Jardine et al., 2020). In contrast, within California we found that temperature was consistently more important than precipitation, and that SLA increases with temperature at both inter‐ and intraspecific levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hietz et al 2011;Willis et al 2017;Koski et al 2020;reviewed in Lang et al 2018); to fill in gaps in sparse trait databases (Queenborough and Porras 2014;Perez et al 2020); or to conduct comparative studies of clades whose species are hard to sample all at once (e.g. Jardine et al 2020). Measuring functional traits on herbarium specimens carries the promise of letting us reach the inaccessible, including the past or distant parts of the world.…”
Section: Introductionmentioning
confidence: 99%